Key Factors Influence on Decision Making to IoT Adoption in Telecommunication Companies: A Review - Abdulwahab Anaam, Elham; Naser Yousef Magableh, Muhamad; Ridha Khudhur, Ahmed; Hussein Abdulallah, Sadoon (International Journal of Engineering and Technology, 2022)
In the context of the impact of advertisement IOT technology, the paper seeks to clarify the critical issues, specifically for telecommunication that deals with the novel technology but sometimes become complex because That is impacted by the constant changes in the information and communication technologies sector, that further leads to high operating expenses for organizations recent technological acquirement, installation, staff training for proper use of every new technology, and costly agreements to the Internet of Things suppliers for the implementation of IoT applications. The decision to adopt IoT technology will assist in predicting the best moment for a prominent telecommunications provider to deploy IoT systems, combining new mobile technologies and densifying its current network at an unmatched rate in the following years. Given the rising relevance of decision-making to IoT adoption and there is a lack of investigation and comparison of decision-making criteria with IoT platforms in this field. This article aims to provide four key factors that influence IoT adoption decision-making in a telecommunication company. Depending on the value of net theory, this article outlines four technical characteristics that influence decision-making in IoT adoption in a telecommunication company. The findings identification are the main factors for telecommunications companies to successfully token decision-making to IoT technology adoption. Â Keywords: Decision Making; IoT Adoption; Telecommunication Company; and Key Factors. Â